A Case of Whistle as Foreign Body in Trachea - Puspa Zuleika (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Most of foreign body aspiration cases are found in children under the age of fifteen. Pediatric patients often presents with non-food foreign body aspiration, such as toys. The most common clinical manifestation are history of choking following foreign object insertion into the mouth (85%), paroxysmal cough (59%), wheezing (57%) and airway obstruction (5%). Case presentation. Main principle of airway foreign body extraction is to do it immediately in the most optimal condition with slightest possible trauma. Rigid bronchoscopy is a suitable choice for tracheal foreign body extraction. We reported a case of seven years old male with tracheal foreign body presented with history of whistle ingestion five hours prior to admission. This patient was discharged from hospital after third days of rigid bronchoscopy procedure. Conclusion. History of foreign body aspiration in children should be suspected as a tracheobronchial foreign body. Rigid bronchoscopy is preferred to extract foreign bodies present in the trachea. The prognosis for tracheobronchial foreign body aspiration is good if the foreign body is treated early and without complications.